Virtual reality training and assessment in laparoscopic rectum surgery. Issue 2 (3rd April 2014) - Pan, Jun J.; Chang, Jian; Yang, Xiaosong; Liang, Hui; Zhang, Jian J.; Qureshi, Tahseen; Howell, Robert; Hickish, Tamas
Abstract Background Virtual‐reality (VR) based simulation techniques offer an efficient and low cost alternative to conventional surgery training. This article describes a VR training and assessment system in laparoscopic rectum surgery. Methods To give a realistic visual performance of interaction between membrane tissue and surgery tools, a generalized cylinder based collision detection and a multi‐layer mass–spring model are presented. A dynamic assessment model is also designed for hierarchy training evaluation. Results With this simulator, trainees can operate on the virtual rectum with both visual and haptic sensation feedback simultaneously. The system also offers surgeons instructions in real time when improper manipulation happens. The simulator has been tested and evaluated by ten subjects. Conclusions This prototype system has been verified by colorectal surgeons through a pilot study. They believe the visual performance and the tactile feedback are realistic. It exhibits the potential to effectively improve the surgical skills of trainee surgeons and significantly shorten their learning curve. Copyright © 2014 John Wiley & Sons, Ltd.